Jogtörténeti és filológiai adalékok az orvoslás kérdésköréhez a Lex Baiuvariorumban - Nótári Tamás (Középkortörténeti tanulmányok, 2017)
This study intends to analyse the provisions of some early medieval "German" legislation concering medical issues, i.e. curing, diseases and injuries. From this scope we shall analyse the regulation of diseases, miscarriage, bodily injury and injuries in the 1-ex Baiuvariorum, that shall be compared with the provisions of some other German leges. In this paper we shall examine the legal consequences of diseases influencing legal capacity and capability of proceeding under the law, the state of facts of abortion, appearance of the involvement of the physician and the treatment applied by him in the text of the law and folk language terminology of bodily injury and injuries.